Factors Causing Stunting In Toddlers In West Sumatra And Its Relationship With Sanitation And Environmental Hygiene : Literatur Review - Nabila Azzahra Azzahra; Abdul Razak; Elsa Yuniarti; Linda Handayuni (JURNAL RISET GIZI, 2024)
One of the health problems that occurs in the world is stunting. Stunting or what is commonly known as short toddlers is a condition where toddlers are less tall compared to their age. West Sumatra Province is ranked 17th out of 34 provinces that experience stunting with a prevalence of stunting in toddlers (aged 24-59 months) of 36.2%, which is higher than the national prevalence, namely 30.8%. Stunting can also occur due to direct factors of stunting such as maternal nutrition during pregnancy, toddler nutrition and disease infections. Apart from direct factors, there are also indirect factors that can occur from various aspects, one of which is water, sanitation and hygiene (WASH). This research uses a literature study method using PICO. The research results obtained were that there was a relationship between the LBW factor (lower baby weight) and the incidence of stunting in toddlers, three articles were obtained. Two articles were found regarding the relationship between exclusive breastfeeding and MP-ASI. On the relationship between parenting styles, four articles were found. Three articles were found regarding the relationship between sanitation and the environment. Three articles were found regarding the relationship between height and height. One article was found regarding the relationship between zinc levels. On the relationship between mother's work, one article was found. Regarding the history of infectious diseases, one article was found. One article was found regarding the relationship between the age of pregnant women and the incidence of stunting in toddlers. From the conclusion above regarding the relationship between environmental sanitation and hygiene on stunting among toddlers in West Sumatra, the most common one is parenting patterns in children.Keyword : abstract; nutrition; words; research